Ontology Conception of Transdisciplinary Scientific Research - Palagin, A.V. (Электронное моделирование, 2016)
One of the highest priority directions of modern community development is building a knowledge-oriented society (as a type of stage of information community development), in which most working people are in the line of work related to creation, saving, processing and implementation of information, especially its (information’s) highest form—knowledge. Among other important problems, which are resolved at the current point of societal development, the problem of providing scientifically grounded, effectively presented and complete informational resources is especially worth emphasizing. Одним из наиболее приоритетных направлений развития современного сообщества является построение общества, ориентированного на знание как стадию развития информационного сообщества, в котором большинство трудящихся занимаются работой, связанной с созданием, сохранением, обработкой и использованием информации, особенно ее высшей формы — знания. Среди других важных проблем, решаемых на современном этапе общественного развития, следует отметить проблему обеспечения научно обоснованными, эффективно представленными и полными информационными ресурсами. Одним з найприорітетнійших напрямків розвитку співтовариства є побудова суспільства, орієнтованого на знання як стадію розвитку інформаційного співтовариства, в якому більшість працюючих, зайняті роботою, пов’язаною із створюванням, збереженням, обробкою та використанням інформації, особливо її найвищої форми — знання. Серед інших важливих проблем, вирішуванним на сучасному етапі суспільного розвитку, слід відзначити проблему забезпечення науково обґрунтованими, ефективно представленими і повними інформаційними ресурсами.